2013
DOI: 10.1002/jor.22423
|View full text |Cite
|
Sign up to set email alerts
|

Use of dithiothreitol to improve the diagnosis of prosthetic joint infections

Abstract: Diagnosis of prosthetic joint infections (PJIs) remains a challenge for microbiologists, despite new techniques for bacteria isolation have been developed in recent years. A widely recognized standard method has not yet been indicated mainly because of limitations due difficult procedures and need of dedicated instrumentation. We evaluated the ability of a sulfhydryl compound routinely used in microbiology laboratories, dithiothreitol (DTT), to dislodge bacteria from biofilm, keeping them alive and cultivable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
3
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 33 publications
1
68
3
2
Order By: Relevance
“…DTT has been recommended for tissue processing because of its high sensitivity, specificity, practicability, and relatively low cost [14, 15]. In this study, DTT was found to be as safe as homogenization in terms of bacterial viability.…”
Section: Discussionmentioning
confidence: 71%
“…DTT has been recommended for tissue processing because of its high sensitivity, specificity, practicability, and relatively low cost [14, 15]. In this study, DTT was found to be as safe as homogenization in terms of bacterial viability.…”
Section: Discussionmentioning
confidence: 71%
“…Biofilm formation may explain the phenomenon of culture-negative PJI. Novel methods, including DL-dithiothreitol and polymerase chain reaction using various probes, are being developed in order to improve the ability of microbiological culture in detecting the pathogenic causes of PJI (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…The theory behind this method is DTT would alter the extracellular matrix of biofilm and free bacteria from it. Using this method on 76 explanted septic and aseptic prosthesis, the authors observed that it improved the sensitivity of sonication (71 % vs 86 %) while its specificity remained similar (94 %) [37]. Use of other molecular techniques for improvement of culture results, such as polymerase chain reaction (PCR) using different probes has also been suggested [38,39].…”
Section: Diagnosismentioning
confidence: 99%